The effect of microvascular decompression of the CN IX-X root entry/exit zone and the ventrolateral medulla in neurogenic hypertension involving the vertebral/basilar artery - Zeng, Defeng; Wang, Shiyao; Wei, Xingrong; Zhang, Shuguang; Zhou, Hao; Hu, Xueqian; Fu, Xin; Li, Yang; Wei, Zhenqing (Frontiers in Neurology, 2024)
Background: Neurogenic hypertension(HTN) is a type of HTN characterized by increased sympathetic activity. Vascular compression is one of the pathogenic mechanisms of neurogenic HTN. Despite Jannetta's solid anatomical and physiological arguments for neurogenic HTN in the 1970s, the treatment for essential HTN by microvascular decompression (MVD) still lacks established selection criteria. Therefore, the subjects selected for our center were limited to patients with primary trigeminal neuralgia(TN) and primary hemifacial spasm (HFS) of vertebral/basilar(VA/BA) artery responsible vessel type coexisting with neurogenic HTN who underwent brainstem MVD to further explore possible indications for MVD in the treatment of neurogenic HTN.Methods: Retrospective analysis of 63 patients diagnosed with neurogenic HTN were treated at our neurosurgery department from January 2018 to January 2023, all of whom had symptoms of HFS and TN cranial nerve disease. Preoperative magnetic resonance examination of the patients suggested the presence of abnormally located vascular compression in the rostral venteolateral medulla (RVLM) and the root entry zone(REZ) of the Ⅸ and X cranial nerves. Results: There was no significant difference in gender, age, course of HFS, course of TN, course of HTN, grade of HTN and preoperative blood pressure between the two groups. Based on postoperative blood pressure levels, 9 of 63 patients were cured (14.28%)、8 cases (12.70%) with marked effect、16 cases(25.40%) with effective、30 cases with Invalidity(47.62%), overall effectiveness 52.38%. However, 39 cases of combined cranial nerve disease were on the left side effective rate(66.67%); 24 cases of combined cranial nerve disease were on the right side effective rate(29.16%).Conclusions: MVD is an effective treatment for neurogenic HTN. Indications may include: left-sided TN or HFS combined with neurogenic HTN,VA/BA artery compression in the left RVLM and REZ areas on MRI; and blood pressure in these patients can not be effectively controlled by drugs.